A new species of Bisaltes Thomson, 1868 from Peru and Ecuador (Cerambycidae, Lamiinae, Apomecynini) - Juárez-Noé, Gino; González-Coronado, Uzbekia; Bezark, Larry G. (Zootaxa, 2022)
A new species of Bisaltes Thomson, 1868 from Peru and Ecuador is described and illustrated: Bisaltes (Bisaltes) confusa sp. nov. Additionally, Bisaltes (Bisaltes) fuscomarmoratus Breuning, 1966 is excluded from the Ecuadorian fauna.